Simultaneous controllers for stabilizing the frequency changes in deregulated power system using moth flame optimization - Peddakapu, kurukuri; Mohd Rusllim, Mohamed; Srinivasarao, P.; Leung, Puiki (Elsevier Ltd, 2022)
This paper introduces a stochastic idea for two-area automatic generation control (AGC) of the restructured system for enhancing the system dynamic performance. In this work, a new 2-degree of freedom of proportional-integral derivative-fractional order proportional derivative with filter (2DOF PID-FOPDN) approach is proposed for the AGC two area system. To ensure realization of optimal gains of the controller, a novel nature-inspired moth-flame optimization (MFO) is suggested using integral of time multiplied absolute error (ITAE) model. The performance of MFO-based 2DOF PID-FOPDN is evaluated against Cuckoo search (CS), Bat algorithm (BA), and Teaching learning-based optimization (TLBO) approaches in different contract scenarios of deregulated system. Further work to reduce the changes in tie-line has been applied through different FACTS controllers, such as Distributed power flow controller (DPFC), Thyristor-controlled series capacitor (TCSC), Unified power flow controller (UPFC), and Static synchronous series compensator (SSSC); integrated into the AGC system with the co-ordination of Ultra-capacitor (UC). The results indicate that the MFO-based 2DOF PID-FOPDN shows superior performance with DPFC-UC over other approaches in all contract scenarios of liberalized system. A sensitivity analysis is examined to recognize the robustness of the suggested approach under ± 25% deviation in loading and system parameters.